Determination of barbiturates in hair samples by using a validated UHPLC-HRMS method: application in investigation of drug-facilitated sexual assault - Di Wen; Yan Shi; Xiaoguang Zhang; Bing Xie; Wenqiao Liu; Feng Yu; Ping Xiang; Bin Cong; Chunling Ma (Oxford University Press, 2019)
In recent years, benzodiazepines and benzodiazepine-like drugs are the most common substances associated with drug-facilitated sexual assaults (DFSA); however, barbiturates are also detected occasionally. Segmental hair analysis provides useful information on the historic pattern of drug use, enabling differentiation between single exposure in DFSA cases and chronic use. However, sensitive and specific methods for barbiturate analysis in hair samples are needed. Herein, we present an ultra-high-performance liquid chromatography coupled with high-resolution mass spectrometry (UHPLC-HRMS) method for qualitative and quantitative determination of seven barbiturates in hair samples. Firstly, a hair strand was decontaminated and then freeze-milled in liquid nitrogen. Next, 50 mg of powdered hair was extracted with methanol in an ultrasonic bath for 10 min in the presence of 10 ng phenobarbital-d5. The supernatant was dried under nitrogen gas, and the pellet was dissolved in 100 µL mobile phase. Afterwards, 10 µL of the suspension was injected into the UHPLC-HRMS system. The present method involved two UHPLC conditions for determination of barbiturates (I) and identification of the structural isomers amobarbital and pentobarbital (II). This method showed satisfactory linearity in a range of 0.02-20.00 ng/mg for UHPLC conditions I and II, both with a high determination coefficient (0.9991-0.9999). The selectivity, intra- and interday precision, accuracy and matrix effect of the method were acceptable. Next, the validated method was applied to investigate an authentic DFSA case. Hair samples (black, approximate 25 cm long) were collected 3 months after the assault, and the proximal segments (0-5 cm from the root; each segment was 1 cm long) were analyzed. Amobarbital was detected at a concentration of < LOQ (limit of quantification) and 0.09 ng/mg in the second and third 1 cm hair segment but not in the other segments. Thus, our method was successful in determining barbiturate concentration in human hair after a single-dose exposure, showing its potential for application in the investigation of DFSA cases.